PLATELET COUNT AND MEAN PLATELET VOLUME AS PROGNOSTIC MARKERS OF UROSEPSIS - Harmaya, Andri Kusuma; Soebadi, M Ayodhia; Soetojo, Soetojo (Indonesian Urological Association, 2018)
Objective: To know and determine platelet count (PLT) and mean platelet volume (MPV) as prognostic factor for outcome in patients with urosepsis. Materials & Methods: This was an analytic observational study. Thirty patients were assigned to the test for PLT and MPV at the day of admission, 36 hours and 72 hours after admission. All subjects were managed according to standard urosepsis therapy. At the 28th day of treatment, patients were evaluated and classified the outcome as survivors and non-survivors. The statistical analysis was performed using multivariate logistic regression with software SPSS 21. In all tests, p<0.05 was considered to indicate significance. Results: The mean of PLT in non-survivors was lower than that in survivors at the day of admission (420 ± 343.57 x103/mm3 vs 423.04 ± 220.15 x103/mm3, p=0.838). Decrease in PLT during the first 72 hours after hospitalization in non-survivors (Δ PLT72h) was greater than that in survivors (-143.43 ± 154.15 x103/mm3 vs -51 ± 121.77 x103/mm3, p=0.050). The mean of MPV in non-survivors was lower than that in survivors at the day of admission (6.30 ± 0.53 fL vs 7.25 ± 1.78 fL, p=0.333). Increase in MPV during the first 72 hours after hospitalization in non-survivors (Δ MPV72h) was greater than that in survivors (3.51 ± 0.86 x103/mm3 vs 1.48 ± 1.54 x103/mm3, p=0.028). In multivariate analysis, Δ MPV72h was an independent predictor of 28-day mortality [OR 9.41 (95% CI, 1.27 – 69.81)]. Conclusion: An increase in MPV during the first 72 hours after hospitalization can be used as poor prognostic in urosepsis patients.